+0  
 
+2
70
1
avatar+917 

1. y = 2x^2 + x - 1

    y = -x - 3

 

2. y = -2x^2 - 2x + 3

    y = 7/2

GAMEMASTERX40  Apr 17, 2018
edited by GAMEMASTERX40  Apr 17, 2018

Best Answer 

 #1
avatar+794 
+1

Substituting y = - x - 3 into the first equation, we have: 

 

- x - 3 = 2 x ^ 2 + x -1 

 

Simplifying, we have: 

 

2 x ^ 2 + 2 x + 2 = 0

 

x=-\frac{1}{2}+i\frac{\sqrt{3}}{2},\:x=-\frac{1}{2}-i\frac{\sqrt{3}}{2}

 

Substituting y = 7/2 into the first equation, we have: 

 

7/2  = - 2 x ^ 2 - 2 x + 3

 

Simplifying, we have: 

 

2 x ^ 2 + 2 x + 2 = 0

 

x=-\frac{1}{2}

 

Since you already know one value, you can plug it in to figure out the other variable. 

GYanggg  Apr 17, 2018
 #1
avatar+794 
+1
Best Answer

Substituting y = - x - 3 into the first equation, we have: 

 

- x - 3 = 2 x ^ 2 + x -1 

 

Simplifying, we have: 

 

2 x ^ 2 + 2 x + 2 = 0

 

x=-\frac{1}{2}+i\frac{\sqrt{3}}{2},\:x=-\frac{1}{2}-i\frac{\sqrt{3}}{2}

 

Substituting y = 7/2 into the first equation, we have: 

 

7/2  = - 2 x ^ 2 - 2 x + 3

 

Simplifying, we have: 

 

2 x ^ 2 + 2 x + 2 = 0

 

x=-\frac{1}{2}

 

Since you already know one value, you can plug it in to figure out the other variable. 

GYanggg  Apr 17, 2018

11 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.